Synthesis and Antimicrobial Activity of New 2-Phenylethynylbenzothiazoles and Related Salts - Magdolen, Peter; Zahradník, Pavol; Foltínov, Pavlína (Arzneimittelforschung, 2000)
New 2-phenylethynylbenzothiazoles were synthesized by coupling reaction between 2-iodoben-zothiazole and substituted phenylacetylenes under palladium catalysis. The modified Wittig reaction was used to prepare the substituted phenylacetylenes from corresponding benzaldehydes. 2-Phenylethynylbenzothiazoles were next quarternized with trimethyloxonium tetra-fluoroborate to 3-methylbenzothiazolium salts. Antimicrobial in vitro activities were determined for all new compounds.
Keywords: Benzothiazoles, antimicrobial activity, synthesis; Benzothiazolium salts, antimicrobial activity, synthesis